Caracterização biometrica, coproparasitologica e do perfil bioquímico de periquitos-da-caatinga (Eupsittula cactorum) de vida livre e cativeiros ilegais do RN e BA - Santana, Vanessa Silva (Universidade Federal Rural do Semi-Árido, 2021)
The determination of biochemical parameters in blood is a tool to aid in the diagnosis of metabolic diseases, define the nutritional profile of a population and allow a more in-depth clinical assessment of individuals. In the poultry clinic, it is common to use reference standards based on the literature, where samples with a small number of animals were used, which were not correctly characterized and without detailed descriptions of the methodologies used for laboratory tests. Despite the existence of several standardized techniques for the study of domestic animals that can also be useful for wild species, there is still a lack of reference standards for many wild bird species. Although captive birds can present diseases similar to those observed in the wild, there is a lack of clinical, epidemiological and laboratory data that limit the diagnosis of metabolic and/or nutritional diseases. In Brazil, the illegal maintenance of animals from hunting is cultural, which ends up culminating in a practice without veterinary care for these animals. This leads to management errors in breeding, especially with regard to proper nutritional management, causing harm to the health of the animals. Through the sampling of animals from seizures and the capture and sampling of free-living animals in pre-established regions, the present work aims to compile data on normal biochemical parameters of neotropical parrots available in the literature, compile data on altered biochemical parameters of Neotropical parrots available in the literature, characterize references of normal biochemical parameters for Eupsittula cactorum and compare with the biochemical parameters of animals of the same species arising from seizure and identify intestinal parasites of free-living Eupsittula cactorum and arising from seizure. In relation to sex, analyzing all animals, as means of CK, FA and GGT were the highest in high. Alkaline Phosphatase (AF) differentiates statistical differences in values when compared between sex and age. AST also show different values when compared between sexes and ages. GGT showed the difference in values between sexes. With respect to measurements, body mass (weight) difference between sex and age. Young animals differences in weight, tarsus and total length measurements. In the coproparasitological evaluation of free-living animals, 57.14% were negative and 14.28% positive for non-sporulated coccidian oocysts; 21.42% positive for coccidia and 7.14% positive for coccidia and eggs of the Trichostrongylidae family. In the evaluation of the animals of apprehension, 11.62% were positive for coccidial oocysts
Keywords: Bioquímica sanguínea; Eupsittula cacotorum; Enzimas hepáticas; Enzimas renais; Endoparasitas; Blood biochemistry; Eupsittula cacotorum; Liver enzymes; Kidney enzymes; Endoparasites; CIENCIAS AGRARIAS::MEDICINA VETERINARIA